2009
DOI: 10.1007/s10689-009-9233-0
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte recruitment into the tumor site is altered in patients with MSI-H colon cancer

Abstract: The ability of the host to mount an appropriate immune response to aberrant cells is one factor that determines prognosis in cancer patients. Naturally occurring regulatory T cells (T regs; CD4+ CD25+ cells) are key regulators of peripheral tolerance. It has been suggested that high levels of T regs are detrimental to the patient in some forms of cancer, but the role of these antigen-specific cells in individuals with colorectal cancers with high levels of microsatellite instability is unknown. Herein, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 68 publications
(83 reference statements)
2
31
0
3
Order By: Relevance
“…Another speculative possibility is that BRAF-mutant tumors may have an altered immune response. MMR-deficient tumors have been shown to be associated with a high density of cytotoxic (CD8+) T and memory (CD45RO+) T cells and may be responsible for the good prognosis associated with MMR-deficient tumors (4244). One of the roles of the activated BRAF/MAPK pathway is immune evasion by the suppression of immunosuppressive factors and inflammatory cytokines, such as interleukin (IL)-10 (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another speculative possibility is that BRAF-mutant tumors may have an altered immune response. MMR-deficient tumors have been shown to be associated with a high density of cytotoxic (CD8+) T and memory (CD45RO+) T cells and may be responsible for the good prognosis associated with MMR-deficient tumors (4244). One of the roles of the activated BRAF/MAPK pathway is immune evasion by the suppression of immunosuppressive factors and inflammatory cytokines, such as interleukin (IL)-10 (45).…”
Section: Discussionmentioning
confidence: 99%
“…One of the roles of the activated BRAF/MAPK pathway is immune evasion by the suppression of immunosuppressive factors and inflammatory cytokines, such as interleukin (IL)-10 (45). IL-10 has been shown to be required for optimal promotion and sustainment of T-cell memory in a mouse model with IL-10 knockout mice (42, 45). However, if BRAF-mutant tumors have an altered interaction with memory T cell, it is not likely to be the result of a decrease in the density of these cells in the primary tumor because higher density of memory T cells (CD45R0) are also associated with BRAF-mutant tumors (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a positive correlation between apoptosis rates and higher TIL number has been described, a finding which could perhaps help to explain the improved prognosis seen in patients with MSI-H compared to MSS tumors [98,101] . Studies on T-regs such as FOXP3 and CD25+ have recently been undertaken [102] . Drescher et al [102] , evaluating both MSS and MSI-H cancers found that in contrast to CD8+ T-cells which may be involved in actively preventing growth and/or metastatic in MSI-H tumors, CD25+ cell counts were similar between MSS and MSI-H tumors suggesting no active immunosuppressive mechanisms in MSS cancers.…”
Section: The Invasive Front Of Colorectal Cancer: Msimentioning
confidence: 99%
“…Studies on T-regs such as FOXP3 and CD25+ have recently been undertaken [102] . Drescher et al [102] , evaluating both MSS and MSI-H cancers found that in contrast to CD8+ T-cells which may be involved in actively preventing growth and/or metastatic in MSI-H tumors, CD25+ cell counts were similar between MSS and MSI-H tumors suggesting no active immunosuppressive mechanisms in MSS cancers. Finally, the upregulation in MSI-H cancers of a large number of genes involved in immune response and increased levels of pro-inflammatory cytokines and cytotoxic mediators indicate an activated anti-tumor immune response in these tumors [86] .…”
Section: The Invasive Front Of Colorectal Cancer: Msimentioning
confidence: 99%
“…It should be noted that the increase of rate of lymphocyte infiltration in tumor tissue after mono or combined therapy is one probable mechanism of inhibition of primary tumor (Fig. 3, a) [22][23][24].…”
Section: Combined Influence Of Teichoic Acids From Staphylococcus Aurmentioning
confidence: 99%